Experimental and finite element analysis for adhesive bonded joints - Wei, Linghong. (2008)
This project presented the analysis of the shear stress distribution experienced at the bondline of the adhesive bonded splice joints subjected to axial tensile load on the ends of substrates. Two joint configurations were considered, namely “Normal Doubler” joint and “Stepped Doubler” joint. A uni-axial tension test was carried out as a study on the shear stress distribution at the bondline of the adhesive bonded joints. A finite element analysis was conducted to simulate the specimen behavior using Finite Element Software ANSYS and the results were verified by a series of experiments.